(untitled) (Environment & Health, 2018)
Objectives: We scientifically substantiated and developed the basic criteria for the assessment and algorithm of the decision-making for informing of the consumers about quality of drinking water and state of drinking water supply, based on the requirements of European legislation. Materials and methods: We analyzed European and Ukrainian normative documents on the quality of drinking water and the need for informing of the consumers and evaluated the questionnaire survey of the population on the quality of tap water (658 questionnaires) in different settlements of Ukraine. We used bibliographic, sociological (questioning), sanitary-and-hygienic methods and method of expert assessment. Results: This paper is the first to unify and to show schematically the algorithms of the procedure of customer informing about the quality of drinking water and the state of drinking water supply according to the requirements of Directive 98/83/EU on drinking water quality for human consumption in order to establish the customer information mechanism and to prevent the use of water sources without quality control. First in the country, we proposed to introduce the unified forms for informing of the customers of drinking water and defined the conditions of informing. Criteria for drinking water quality assessment in case of the over-standard content of “indicator parameters” were developed.